Compensatory Legitimation of Emir Sayyid Abd Al-Ahad Khan’s Authority (1885–1910) Under the Russian Protectorate: Religious-Dynastic and Representational Practices - Vakhabov Azizjon Khamidovich (American Journal Of Social Sciences And Humanity Research, 2026)
This article examines the political portrait of the Emir of Bukhara, Sayyid Abd al-Ahad Khan (r. 1885–1910), through the analytical framework of his legitimation which was mainly compensatory as the dependency on the Russian empire kept increasing. Drawing on Russian, local (Bukharan/Uzbek), and selected Anglophone sources, the study argues that the emir’s authority was sustained not only by external support - above all Russian recognition and diplomatic patronage - but also by internal symbolic and political mechanisms, including dynastic sacralization, genealogical constructions, religious projects, courtly representation, gift exchange, and public charity. Furthermore, the article also identifies limits pertaining to this model: tensions with the religious milieu, the strengthening of favoritism, strains brought about by the ethno-confessionals and a broader crisis of governability. The political image of Abd al-Ahad Khan is mainly portrayed in the sources as a protectorate monarch of a hybrid nature: externally loyalist yet internally positioned as a guardian of sacral status, whose authority increasingly depended on symbolic compensation for diminishing sovereignty.